Hepatitis B virus X protein modulates upregulation of DHX9 to promote viral DNA replication. (12th December 2019) - Shen, Bocun; Chen, Yanmeng; Hu, Jie; Qiao, Miao; Ren, Jihua; Hu, Jieli; Chen, Juan; Tang, Ni; Huang, Ailong; Hu, Yuan
Abstract: Hepatitis B virus (HBV) infection is a major cause of acute and chronic liver diseases. During the HBV life cycle, HBV hijacks various host factors to assist viral replication. In this research, we find that the HBV regulatory protein X (HBx) can induce the upregulation of DExH‐box RNA helicase 9 (DHX9) expression by repressing proteasome‐dependent degradation mediated by MDM2. Furthermore, we demonstrate that DHX9 contributes to viral DNA replication in dependence on its helicase activity and nuclear localization. In addition, the promotion of viral DNA replication by DHX9 is dependent on its interaction with Nup98. Our findings reveal that HBx‐mediated DHX9 upregulation is essential for HBV DNA replication.